Removal energy of a spacecraft using a powered swing-by in an elliptical system - Ferreira, Alessandra F. S. [UNESP]; Moraes, Rodolpho V. [UNESP]; Prado, Antonio F. B. A.; Winter, Othon C. [UNESP] (My University, 2021)
An important application of the powered Swing-By maneuver is to decelerate a spacecraft to insert it into a desired orbit, to keep it captured or just to slow down its passage for a better observation of the body. This maneuver aims to take advantage of the gravity of the body where the close encounter is made with the combination of an impulse applied in some point of the orbit to modify its parameters, among them the energy. The analysis of the loss of the energy of the spacecraft after the maneuver and the best configurations to reach this objective is presented in this work. The study is made for a system whose primary bodies are in elliptical orbit. Regarding the impulse, its direction and points of application are free parameters to get the most from the maneuver.